PERAN PEMERINTAH DAERAH DALAM PENYELESAIAN SENGKETA TANAH DI LAHAN PASIFIC MALL KOTA TEGAL - Rosmiatasari, Reni; Martini, Rina; Astuti, Puji (Journal of Politic and Government Studies, 2013)
ABSTRACTThe study entitled â€œThe Role of Local Government in Land Dispute Resolution in the Land of Mall Pacific Tegal Cityâ€ aims to know the process of land right resolution that is used as Mall Pasific by the government through the court.This study used qualitative approach with descriptive type. Research data were obtained from interview, and observation. analyze of data is done qualitatively through data reduction suitable with subject matter, focused on the study and refers to the principal problem that wished to be answered on this study.Based on the result of the study , it shows that the cause of land dispute in Mall Pasific Tegal land is at government with land owner due to the presence of the right of land management certificate (HPL) owned by tegal local government 16.250 m2 wide on behalf of tegal city government which the right is changed to certificate of proprietary right Number M.613, M.667 and M.704. In the process of land dispute resolution, it revealed truth that the land right published as management right certificate on behalf of Tegal city government by Tegal city land affairs office and the absence of interior minister decision that referred on extending the right of management in the process of publishing the certificate, with the result that judge comitee of Tegal country court detect lie indication and engineering sign from land affairs office official in publishing the right of management certificate, then land certificate was canceled and ask to land affairs office official to return land right to land owner.In addition, another problem related to land dispute is the presence of contract agreement which state, second party (city government) can use the certificate of HGB number 596 Pekauman district and the owned right certificate number M.613, M.667, and M.704 Pekauman District at bank with the agreement of first party (gatot) and obviously it was a land dispute known yet the owner who has the right of the land.Keywords: Role of local government, Land dispute resolution